The Prediction of Macrovascular Complications in Individuals with Type 2 diabetes mellitus with Different Risk Factors in ThiQar - Shahad Turkey Mana,; Dawood Salman Mahdi,; Mahmood Thamer Altemimi, (University of Thi-Qar Journal of Science, 2023)
Background:Diabetes mellitus (T2DM) is a major health issue globally, posing a significant financial and social burden on individuals, families, and communities.The objectives of the present study were to evaluate the risk factors of T2DM and its relationship with macrovascular complications.Methods:A cross-sectional observational study was conducted on 1189 individuals with T2DM attending Thi-Qar Specialized Diabetes Endocrine and Metabolism Center (TDEMC) in Nasiriya City, Thi-Qar, Southern Iraq. All patients All patients’ data were gathered from the direct interviewees and the digital records of TDEMC, which used an internal network system and Microsoft Access Program.Results: The mean age was 55.9 ±11.7 years, female 58%, body mass index 31.2 ±5.5 kg/m2 , waist circumference 108±11.6 cm, One-fifth (20.9%) of this cohort were having an established atherosclerotic cardiovascular.Dyslipidaemia in T2DM was a common biochemical derangement of 77.6% and it increases the risk of all elements of macrovascular complication at a rate of 87.8% P/<0.001 heart disease, (85.4% P/0.015) stroke and (79.6% P/ 0.063) clinical PAD. Hypertension (63.5%), family history of T2DM (64.9%), history of CVD, sign insulin resistance (61.7%), centralobesity (84.3%), history of gestational diabetes mellitus and estimated glomerular filtration rate <60 ml/min/1.73m2 were having a significant effect on overall macrovascular complications among T2DM.Conclusion: History of dyslipidemia is the most significant (p=<0.001) independent risk factor for the prediction ofmacrovascular complications among T2DM, while other risk factors were considered as dependent to further cofounders.